Prognostic implications of a CD8+ TEMRA to CD4+Treg imbalance in mandibular fracture healing: a prospective analysis of immune profiles - Voss, Jan Oliver; Pivetta, Fabio; Elkilany, Aboelyazid; Schmidt-Bleek, Katharina; Duda, Georg N.; Odaka, Kento; Dimitriou, Ioanna Maria; Ort, Melanie Jasmin; Streitz, Mathias; Heiland, Max; Koerdt, Steffen; Reinke, Simon; et al. (Frontiers in Immunology, 2024)
Introduction: Open reduction and fixation are the standard of care for treating mandibular fractures and usually lead to successful healing. However, complications such as delayed healing, non-union, and infection can compromise patient outcomes and increase healthcare costs. The initial inflammatory response, particularly the response involving specific CD8 + T cell subpopulations, is thought to play a critical role in healing long bone fractures. In this study, we investigated the role of these immune cell profiles in patients with impaired healing of mandibular fractures.In this prospective study, we included patients with mandibular fractures surgically treated at Charité -Universitätsmedizin Berlin, Germany, between September 2020 and December 2022. We used follow-up imaging and clinical assessment to evaluate bone healing. In addition, we analyzed immune cell profiles using flow cytometry and quantified cytokine levels using electrochemiluminescence-based multiplex immunoassays in preoperative blood samples.Results: Out of the 55 patients enrolled, 38 met the inclusion criteria (30 men and 8 women; mean age 32.18 years). Radiographic evaluation revealed 31 cases of normal healing and 7 cases of incomplete consolidation, including 1 case of non-union.Patients with impaired healing exhibited increased levels of terminally differentiated effector memory CD8 + T cells (TEMRA) and a higher TEMRA to regulatory T cell (Treg) ratio, compared with those with normal healing.Conclusions: Our analysis of mandibular fracture cases confirms our initial hypothesis derived from long bone fracture healing: monitoring the TEMRA to Treg ratio in preoperative blood can be an early indicator of patients at risk of impaired bone healing. Radiologic follow-up enabled us to detect healing complications that might not be detected by clinical assessment only. This study highlights the potential of individual immune profiles to predict successful healing and may form the basis for future strategies to manage healing complications.